Acanthochondria serrani sp. n. (Copepoda: Chondracanthidae) parasitic on Serranus auriga (Perciformes: Serranidae) from Argentinean waters - Braicovich, Paola E; Timi, Juan T (Folia parasitologica, 2009)
A new species of Acanthochondria Oakley, 1927 (Copepoda, Poecilostomatoida, Chondracanthidae), parasitic on Serranus auriga (Cuvier) from the Argentinean coastal zone, is described and illustrated. The new species differs from its congeners by the relative length of the neck and the protopod of leg 2. This is the second record of this genus for the South-eastern Atlantic and the first one from a serranid host.
Keywords: Perciformes; financování organizované; Animals; Atlantský oceán; Financing, Organized; nemoci ryb; zvířata; Atlantic Ocean; Fish Diseases; Argentina; Copepoda